What the study of voice recognition in normal subjects and brain-damaged patients tells us about models of familiar people recognition - Gainotti, Guido (Neuropsychologia, 2011)
► Voice recognition disorders are mainly due to right temporal lesions. ► Face and voice recognition disorders can both co-occur and dissociate. ► When voice recognition disorders prevail, the superior temporal gyrus is damaged. ► Familiarity feelings are generated in the modality-specific recognition units. ► ‘Familiar-only-experiences’ from face and from voice in normal subjects. In recent years it has been shown that a disorder in recognizing familiar people can be observed in patients with lesions affecting the anterior parts of the temporal lobes and that these disorders can be multi-modal, simultaneously affecting the visual, auditory and linguistic channels that allow person identification. Several authors have also shown that patients with right anterior temporal atrophy are more impaired in assessing familiarity and in retrieving person-specific semantic information from faces than from names, whereas the opposite pattern of performance can be observed in patients with left temporal lobe atrophy. Voice recognition disorders have been studied much less even despite their clinical and theoretical importance. The aim of the present review, therefore, was to compare recognition of familiar faces and voices, taking into account not only results obtained in individual patients with right anterior temporal lesions, but also those of group studies of unselected right- and left brain-damaged patients and results of experimental investigations conducted on face and voice recognition in normal subjects. Results of the review showed that: (1) voice recognition disorders are mainly due to right temporal lesions, similarly to face recognition disorders; (2) famous voice recognition disorders can be dissociated from unfamiliar voice discrimination impairments; (3) although face and voice recognition disorders tend to co-occur, they can also dissociate and in these patients there is a prevalent involvement of the right fusiform gyrus when face recognition disorders are on the foreground, and of the right superior temporal gyrus when voice recognition disorders are prominent; (4) normal subjects have greater difficulty evaluating familiarity and drawing semantic information from the voices than from the faces of celebrities. These data are at variance with models which assume that familiarity feelings may be generated at the level of person identity nodes (PINs) and that the latter may be considered as modality-free gateways to single semantic systems in which information about people is stored in an amodal format.